Two way Panel Causality Analysis for Degree of Trade Openness and Size of City - Uzma Tabassum; Shaista Alam (Journal of Basic & Applied Sciences, 2018)
The relationship between trade openness and economic size of city has long been a subject of much interest in international literature of trade. Trade Openness might increases the economic size of city by increasing the significance of transportation modes which are mostly present in urban areas and raising the demand for marketing, financing and communication. In contrast some literature argue that protectionism generates large cities as firms cluster in an urban area to minimize its unit cost via sharing of intermediate goods, labour pool and knowledge spill-over. Thus, there exist an important causal connection between the economic size of the city and its contribution in international trade. This paper is designed to explore these causal connections using panel causality analysis. The panel consists of fourteen major cities of Pakistan and 14 years commence from 1999-00 till 2012-13. The result affirms a positive two-way causal relationship between a cities’ economic size and its degree of trade openness.